Effects of Preoperative Dehydration on Postoperative Nausea and Vomiting in Gynecological Surgery Patients - Yunjeong Hwang; Somi Park (Korean Society of Women Health Nursing, 2015)
PURPOSE: The purpose of this study was to investigate the effect of dehydration from preoperative fasting on postoperative nausea and vomiting in patients who underwent gynecologic surgeries. METHODS: Study design was a prospective descriptive study. A total of 75 patients in a university hospital were selected. Data were collected from March 17 to May 16, 2014 using self-report questionnaires and clinical electronic chart. RESULTS: Factors influencing the development of postoperative nausea and vomiting were type of surgery (t=3.44, p=.001), use of PCA (t=-2.16, p=.034), and preoperative dehydration level (t=5.93, p<.001), and these variables accounted for 51.7% of postoperative nausea and vomiting. Among these variables, preoperative dehydration amount (beta=.56) showed the largest influence in the difference in postoperative nausea and vomiting. CONCLUSION: Reducing dehydration during preoperative fasting can prevent occurrence of postoperative nausea and vomiting. Development of a clinical guideline is necessary to give directions for the prevention of dehydration during preoperative fasting and to ensure the proper duration of fasting according to patient characteristics, type of surgery and time of surgery.